PP.01.15: ECHOCARDIOGRAPHIC PARAMETERS INVOLVED IN EVOLUTION OF DIASTOLIC DYSFUNCTION IN HYPERTENSIVE PATIENTS WITH ACUTE MYOCARDIAL INFARCTION. (June 2015) - Toader, D.; Mihailovici, A.; Racareanu, A.; Musetescu, R.
Abstract : Objective: Pseudonormal and restrictive diastolic pattern of mitral inflow were associated with dilatation and cardiac mortality in first year after acute myocardial infarction (AMI). Arterial hypertension before the acute coronary event is known to be a factor linked to an increased enddiastolic pressure. Purpose of the study was to find a correlation between echocardiographic parameters of filling pressure at discharge and pattern of mitral inflow at one year after AMI in hypertensive patients. Design and method: A number of 98 hypertensive patients (56 males and 42 females), admitted with acute myocardial infarction with ST-segment elevation were evaluated during the first week by: clinical examination, 12 lead standard ECG, echocardiographic measurement of: left atrium volume index (LAVi), left ventricular mass index (LVMi) using transthoracic echocardiography; cut off levels for left ventricular hypertrophy (LVH) were LVMi>115 g/m2 in males and>95 g/m2 in females; mitral inflow, pulmonary venous inflow measurement using Doppler echocardiography, tissue Doppler echocardiography at lateral and medial corner of mitral annulus, color Mmode echocardiography. E/E' average ratio, E/vp ratio and ar-A duration were calculated. After one year the pattern of mitral inflow was evaluated using transthoracic Doppler echocardiography. All patients received fibrinolytic therapy. LVEF measured by Simpson method was less than 45%. Results: 1. Mean values of parameters of filling pressure in hypertensive patients with LVH and without reperfusion were: VASi:35, 04, p = 0, 00007, E/E':14, 81, p = 0, 03992, E/vp:1, 99, p = 0, 00197, ar-A:28, 79, p = 0, 00726. 2. Using chi squared (CS), odd ratio (OR) and relative risk (RR) significant correlations were found between mitral pattern and: VASi>32 ml/m2 CS:6, 512834; E/E'>14, CS:10, 179653, E/vp < 1, 5, CS:10, 637642, ar-A>30ms, CS:40, 105. Conclusions: 1. The highest mean values of echocardiographic parameters of increased filling pressure at discharge after an acute myocardial infarction were found in hypertensive patients with LVH and without reperfusion. 2. A correlation was found between these increased mean values at discharge and mitral inflow after one year suggesting a worse evolution in these patients.